Fast stabilization of a high-energy ultrafast OPA with adaptive lenses - Negro, Matteo (Sci Rep, 2018)
The use of fast closed-loop adaptive optics has improved the performance of optical systems since its first application. Here we demonstrate the amplitude and carrier-envelope phase stabilization of a high energy IR optical parametric amplifier devoted to Attosecond Science exploiting two high speed adaptive optical systems for the correction of static and dynamic instabilities. The exploitation of multi actuator adaptive lenses allowed for a minimal impact on the optical setup.